Kinks as Goals: Accelerating Commissions and the Performance of Sales Teams - Peter J. Kuhn; Lizi Yu (Institute of Labor Economics (IZA), 2021)
We study the performance of small retail sales teams facing an incentive scheme that includes both a lump sum bonus and multiple accelerators (kinks where the piece rate jumps upward). Consistent with standard labor supply models, we find that the presence of an attainable bonus or kink on a work-day raises mean sales, and that sales are highly bunched at the bonus; inconsistent with those models we find that teams bunch at the kinks instead of avoiding them. Teams' responses to the kinks are consistent with models in which the kinks are perceived as symbolic rewards, and inconsistent with reference point models where kinks induce loss aversion.
Keywords: J33; M12; 330; teams; bonuses; bunching; accelerators; symbolic rewards; loss aversion